تأثير البرامج التلفزيونية العائلية على تعزيز الروابط الاسرية - فاطمة الزهراء دحه; زهيرة عطية (جامعة الوادي - University of Eloued, 2025)
"أجريت الدراسة الموسومة ب البرامج التلفزيونية العائلية على تعزيز الروابط الأسرية دراسة ميدانية بمديمة وادي سوف في الفترة الممتدة من فيفري 2025 إلى 18 ماي 2025 على عينة قوامها 80 أسرة . وتمحورت إشكالية الدراسة في : ما تأثير البرامج التلفزيونية العائلية على تعزيز الروابط الأسرية ؟ وللإجابة على هذا التساؤل تم تقسيمه للأسئلة التالية : 1. ما هي عادات وانماط تعرض الاسر للبرامج التلفزيونية العائلية ؟ 2. كيف تُأثر البرامج التلفزيونية العائلية على العلاقات الأسرية ؟ 3. كيف تُأثر مشاهدة البرامج التلفزيونية العائلية على أفراد الأسرة ؟ وهدفت الدراسة لمعرفة أثر البرامج التلفزيونية على تعزيز الروابط الأسرية وقد إستخدمنا المنهج الوصفي للدراسة من أجل الإلمام بجوانب الموضوع ، والإستبيان كأدة لجمع البيانات في الدراسة الميدانية التي عرضت على عدد من الأسر في ولاية وادي سوف ، كما إعتمدت الدراسة على نظرية الإستخدامات والإشباعات وتحصلت الدراسة على النتائج التالية : ان البرامج التلفزيونيو العائلية تقوم بدور مهم في تعزيز الروابط العائلية والاسرية بين الافراد , حيث تعمل ايضا على اكساب الفرد عادات وانماط للمشاهدة الاجابية لهذه البرامج. " The study entitled “Family Television Programs and Their Role in Strengthening Family Bonds: A Field Study in the City of El Oued” was conducted during the period from February 2025 to May 18, 2025, on a sample consisting of 80 families. The central research problem was: What is the impact of family television programs on strengthening family bonds? To answer this question, it was broken down into the following sub-questions: 1. What are the habits and patterns of families in watching family television programs? 2. How do family television programs affect family relationships? 3. How does watching family television programs affect individual family members? The study aimed to explore the impact of family television programs on strengthening family ties. The descriptive method was used to gain a comprehensive understanding of the topic, and a questionnaire was utilized as a tool for data collection in the field study, which was conducted among several families in the Wilaya of El Oued. The study was based on the Uses and Gratifications Theory. The findings revealed that family television programs play an important role in reinforcing familial and interpersonal bonds. They also contribute to instilling positive viewing habits and patterns among individuals.
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: الروابط الأسرية; تعزيز; البرامج التلفزيونية العائلية; "family television programs; strengthening; family ties